SURGERY BOOK DEDICATED TEACHERS AND STUDENTS IN THE IMPLEMENTATION OF BOOKS PERMENDIKBUD NO.21 AND 22 OF 2016 IN BANDUNG PROVINCE JAWABARAT - Yuni Indriyani; Nurul Fazriyah; Tati Heriati (LPM Universitas Pasundan, 2019)
Teachers in the 2013 curriculum are required to study handbooks published by the government in connection with the mapping of indicators and the suitability of basic competencies with subsequent indicators adjusted to Permendikbud No. 21 and 22 of 2016. But in reality at school teachers do not fully use books Because teacher in the learning process teachers still feel confused using books. The problem faced in this service is how the application of teacher and student books books before Permendikbud 21 and 22 of 2016. The purpose of this service is to find out the extent of understanding of primary school teachers in the application of teacher books and student books before Permendikbud No. 21 and 22, 2016. With book reviews and student teacher books, teachers can better understand how teacher and student books books should be.